Teacher's Journey in Understanding, Interpreting, and Applying the Concept of Merdeka Belajar in IPAS Learning - Zulia Nurul Faizah; Hayuni Retno Widarti; Sri Rahayuningsih; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (Ta'dib, 2024)
The concept of merdeka belajar is a characteristic of the kurikulum merdeka. This concept is the basis for teachers in implementing learning, including in the IPAS subject. The purpose of this study is to describe how teachers understand, interpret, and apply independent learning in IPAS learning as well as efforts to continue to fight for IPAS learning with interesting presentations. Data were obtained through interviews, observations, documentation at SDN Banaran 2 Kandangan Kediri which were then described qualitatively descriptively, analyzed using the Miles and Huberman technique, and validated by triangulation. The results of this study show that the merdeka mengajar platform is a medium for teachers to understand merdeka bealajar, reflection on recognizing themselves and their role as educators as an effort to interpret merdeka bealajar, and the obligation to complete independent training on the merdeka mengajar platform; binding policies from structural education authorities from sub-districts and school clusters; and the absence of guidelines that truly integrate science and social studies in learning are the difficulties of teachers in implementing merdeka bealajar. This research can be a consideration for policy holders, curriculum developers, and education practitioners as an effort to optimally implement the independent curriculum.